The invasive Caribbean Mytilopsis sallei (Bivalvia: Dreissenidae): A short review - Koh Siang Tan; Teresa Tay (ASEAN Journal on Science and Technology for Development, 2018)
The mussel-like bivalve species from the Caribbean, Mytilopsis sallei, is now well established in the vicinities of several ports in South and Southeast Asia. Although it may not be as notorious as its relative the zebra mussel Dreissena polymorpha, this brackish-water bivalve has the ability to colonise and displace native species in intertidal and subtidal habitats. It is also another testament to how well a tropical species can travel beyond its natural biogeographical boundaries. Here we briefly review its taxonomy, morphology, growth and reproduction, habitat and distribution, as well as its impact on natural habitats after invasion, based on published literature.